Evaluation of noise exposure before and after noise barriers, a simulation study in Istanbul. Issue 4 (1st October 2016) - İlgürel, Nuri and Yüğrük Akdağ, Neşe and Akdağ, Ali
Abstract: İstanbul is the most prominent Turkish city in terms of the gradually worsening noise problems associated with the rapid increase in population. This study aims to investigate the noise exposure in the settlements around the link roads connecting the Bosporus Bridge to the European side of the city by the aid of simulations and noise mapping, in the frame of action planning studies performed in İstanbul. Noise maps were generated for Lden and Ln noise indicators with the help of a noise mapping software. Since a considerable part of the settlements is exposed to high noise levels, a noise barrier alongside the link road was proposed as a control measure by the aid of the acoustic simulation. Simulations with the noise barriers suggest that for the Lden time interval the noise affected area over 55 dBA would reduce by 10%, the number of dwellings by 26% and the number of inhabitants by 25%, whereas for the Ln time interval the noise affected area over 45 dBA would reduce by 5%, the number of dwellings by 20% and the number of inhabitants by 20%.